The Implementation of Moral Values in Islamic Learning: Overview The Teachings of the Khalwatiyah Samman Order - Najamuddin, Andi; Mansur; Fatmawati (ETDC: Indonesian Journal of Research and Educational Review, 2024)
This study intends to examine how the teachings of the Khalwatiyah Samman Order instill moral values and implement them in society from the perspective of Islamic religious education. This study employs a qualitative research method, utilizing two distinct approaches: the first, the phenomenal approach, and the second, the sociological approach. The Wajo Regency served as the research location. The first participant observation is the data collection technique used, which examines data based on events that occur, locations, and places where images were recorded as accurate data sources. The study's results demonstrate that the teachings of the Khalwatiyah Samman order align with those outlined in the book Jamial Usuli Fil Uliyai. (1) One of these teachings is Dhikr bi-lisan, a verbal prayer in which a loud voice utters the phrase tauhid lailaha illallah. You must believe this prayer verbally, affirming that Allah is the only god worthy of worship. (2) Dhikr bil qalbi, namely Dhikr that is said in the heart or in the heart, both of these Dhikrs are bil-lisan, namely knowing the existence of God, who alone deserves to be worshipped, asked for help, and this kind of Dhikr will receive good deeds in the sight of Allah SWT. (3) Dhikr bil-ruh, namely Dhikr in this case, Dhikr in a divine atmosphere, namely there is no longer any real form except the form of Allah, all the joints of life for the servant of Allah who knows or has great mahabba (love), (4) Dhikr bil-zir, also referred to as Dhikr, denotes a state where a servant of Allah is genuinely always present with Allah. All of his daily activities possess a high Dhikr that defies words, ink, or wind. Only Allah, the remembered one who performs Dhikr, comprehends this state.